(3CfSGH GdCTQGa hCNHGQges - (3CHh GdMSf CMeO Hf jMji Hf LGHQ Hf OGhO, GdHdGPQj,J (B279 (3g` s
(3ChdgG (B:s
(3bGd CMeO Hf jMji Hf LGHQ (B: (3CNHQfi geGYI ef Cgd GdYde HGdcJH bGdhG s
(3BNQgG (B:s
(3NHQ eMeO Hf GdMfajI hGHf GdRHjQ hYHO Gdedc Hf eQhGf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs